Cost–Utility Analysis of PCSK9 Inhibitors and Quality of Life: A Two-Year Multicenter Non-Randomized Study - José Seijas-Amigo; Maria José Mauriz-Montero; Pedro Suarez-Artime; Mónica Gayoso-Rey; Francisco Reyes-Santías; Ana Estany-Gestal; Antonia Casas-Martínez; Lara González-Freire; Ana Rodriguez-Vazquez; Natalia Pérez-Rodriguez; Laura Villaverde-Piñeiro; Concepción Castro-Rubinos; et al. (Diseases)
The primary objective of this study was to conduct a cost–utility analysis of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in real-world, comparing their use with standard care for managing cardiovascular disease. A multicenter prospective study was conducted across 12 Spanish hospitals from May 2020 to April 2022, involving 158 patients with hypercholesterolemia or atherosclerotic cardiovascular disease. This study assessed health-related quality of life (QoL) using the EQ-5D-3L questionnaire. The cost–utility analysis evaluated the economic impact of PCSK9 inhibitors when used with standard care compared to standard care alone, calculating the incremental cost–effectiveness ratio (ICER). This study included 158 patients with an average age of 61 years, male (66.5%). For patients initiating PCSK9 inhibitors, the treatment cost was EUR 13,633.39, while standard therapy cost EUR 3638.25 over two years. QoL for PCSK9 inhibitors stood at 1.6489 over two years, compared to 1.4548 for standard therapy. The results revealed favorable cost–utility outcomes, with an ICER of EUR 51,427.72. Significant improvements were observed in the domains of mobility, self-care, daily activities, pain/discomfort, and anxiety/depression (p < 0.001). This study presents the first real-world cost–utility analysis of PCSK9 inhibitors, supporting their economic rationale and highlighting their benefits in clinical practice. Healthcare decision-makers can use these results to inform their decisions and reimbursement policies concerning PCSK9 inhibitors. Trial Registration clinicaltrials.gov Identifier: NCT04319081.